Egg yolk IgY antibodies: A therapeutic intervention against group A rotavirus in calves. (December 2015) - Vega, C.; Bok, M.; Saif, L.; Fernandez, F.; Parreño, V.
Abstract: Bovine group A rotavirus (RVA) is considered the major cause of diarrhea in intensively reared neonatal calves. Chicken egg yolk antibodies (IgY) are efficient in protecting neonatal calves from RVA diarrhea; however, the value of this intervention in calves once diarrhea has appeared is unclear. The aim of the present study was to evaluate the application of RVA-specific IgY as a passive treatment in those cases. The experimental groups were: G1 = RVA-specific IgY treatment; G2 = no Ab treatment; and G3 = colostrum deprived + no Ab treatment. IgY treatment significantly reduced virus shedding, diarrhea duration and severity compared to G2 and G3 calves. However, it caused a partial suppression of systemic Ab responses to RVA that could be associated with less severe diarrhea. The oral treatment with IgY for 7 days was associated with significantly higher antibody secreting cell responses in the calves compared with other groups of animals. Highlights: Neonatal calf diarrhea is a critical problem and passive therapy with IgY Abs is a way to control it. There are no solid studies using rotavirus specific IgY Abs once calves suffer from diarrhea. We provide here scientific information regarding the effects of IgY-based products. This information is critical considering that IgY Abs are being sold in several countries. We prove the therapeutic value of IgY-based treatment and the industrialization of this product.